Molecular Dynamics simulations of supercritical ammonia and metal-ammonia solutions - Hannongbua, S.; Kiselev, M.; Heinzinger, K. (Condensed Matter Physics, 2000)
The results of Molecular Dynamics simulations of supercritical ammonia are reported for the ﬁrst time. Qualitative agreement is found with neutron diffraction studies, the only experimental evidence on the structure of supercritical ammonia, so far. Based on the experiences with aqueous electrolyte solutions, it is discussed how the potentials describing ion-ammonia interactions in dilute and concentrated metal-ammonia solutions at subcritical conditions have to be modiﬁed for supercritical simulations. Вперше представлені результати моделювання методом молекулярної динаміки аміаку в надкритичному стані. Встановлено якісне узгодження з дослідженнями за дифракцією нейтронів, які є єдиним експериментальним свідченням про структуру аміаку у надкритичному стані. На основі відомих даних про водні розчини електролітів обговорюється питання про те, в який спосіб необхідно модифікувати потенціали, що описують взаємодії іон-аміак у розведених та концентрованих розчинах металів у аміаку, з метою їх застосування у моделюванні аміаку в надкритичному стані.